2011
DOI: 10.1111/j.1744-9987.2011.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Oxidative Stress and Dyslipidemia in Dialysis Patients

Abstract: Our aim was to investigate and determine the associations between oxidative stress (OS), dyslipidemia and inflammation in patients treated with continuous ambulatory peritoneal dialysis (CAPD) and hemodialysis (HD) using observational cross-sectional study. Twenty patients in CAPD and 48 in HD for at least 8 weeks and aged ≥18 years were included in the study. Individuals with malignant or acute inflammatory disease were excluded. A control group of 17 healthy individuals was also recruited. The biochemical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 23 publications
3
21
0
2
Order By: Relevance
“…The disulfide/native thiol levels were also different between the three groups; the disulfide/native thiol levels were slightly higher in the transplantation and PD groups compared to the HD group. While these results are consistent with few other previous studies, increased levels of oxidative stress in HD compared to those in PD have also been reported in some studies (20)(21)(22)(23)(24). We believe that the increased oxidative stress observed in the PD patients (compared to those in the HD patients) in our study may have been caused by inflammatory responses.…”
Section: Discussionsupporting
confidence: 53%
“…The disulfide/native thiol levels were also different between the three groups; the disulfide/native thiol levels were slightly higher in the transplantation and PD groups compared to the HD group. While these results are consistent with few other previous studies, increased levels of oxidative stress in HD compared to those in PD have also been reported in some studies (20)(21)(22)(23)(24). We believe that the increased oxidative stress observed in the PD patients (compared to those in the HD patients) in our study may have been caused by inflammatory responses.…”
Section: Discussionsupporting
confidence: 53%
“…Also, it is not known whether oxidative stress varies with dialysis modality. In a few studies, increased levels of oxidative stress have been reported to be associated with hemodialysis (HD) compared with peritoneal dialysis (PD) (18,19), but other studies showed the opposite results (20)(21)(22).…”
mentioning
confidence: 99%
“…Esta é uma das razões pelas quais há níveis anormais de lipídeos na resistência à insulina. Elevados níveis de lipoproteína de baixa densidade ligada ao colesterol (LDL-c) e baixos níveis de HDL-c, além de aumentos nos níveis de proteína C reativa, também se relacionam com os radicais livres em diferentes estudos [29][30][31][32][33].…”
Section: /7unclassified
“…Observa-se elevação de marcadores de estresse oxidativo em modelos animais quando há níveis elevados de LDL-c e baixos níveis de HDL-c e, em seres humanos, observa-se elevação destes marcadores quando há hipertrigliceridemia e baixos níveis de HDL-c. Medicações hipocolesterolemiantes, como algumas estatinas, podem reduzir o estresse oxidativo porque aumentam a síntese de enzimas antioxidantes, como glutationa peroxidase, catalase e superóxido dismutase [3,29,31,35].…”
Section: /7unclassified